2004
DOI: 10.17221/4071-pse
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic compounds in the leaves and roots of radish grown in three soils treated by dimethylarsinic acid

Abstract: The effect of dimethylarsinic acid (DMA) on the growth of radish and the content of As compounds in roots and leaves of the radish were investigated. Radish was grown in pots in three soils (Fluvisols, Chernozems and Luvisols) amended with 20 mg As/kg of soil in form of DMA. Behavior and transformations of DMA in the soils differed depending on the individual soil type. In the first season, plants grew up at Luvisols only. In the second season the plants were able to grow at Luvisols and Chernozems, too. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Mäkelä-Kurtto et al [10] found in Pirkanmaa region (Finland) that in arable soil, only about 1% of total arsenic was in soluble forms, and the arsenic content was higher in the lower mineral layers. Tlustoš et al [11] observed that the presence of dimethylarsinic acid (DMA) in soil strongly affected the radish growth and the soil properties; the lowest As immobilization was found in Fluvisols while was higher in Luvisols and Chernozems. This was explained on the basis that Fluvisols are characterized by poor sorption capacity and low clay particle content, so that DMA remains available for plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Mäkelä-Kurtto et al [10] found in Pirkanmaa region (Finland) that in arable soil, only about 1% of total arsenic was in soluble forms, and the arsenic content was higher in the lower mineral layers. Tlustoš et al [11] observed that the presence of dimethylarsinic acid (DMA) in soil strongly affected the radish growth and the soil properties; the lowest As immobilization was found in Fluvisols while was higher in Luvisols and Chernozems. This was explained on the basis that Fluvisols are characterized by poor sorption capacity and low clay particle content, so that DMA remains available for plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The contents of mobile Cd slightly exceed the proposal of mobile Cd content limit in agricultural soils of the Czech Republic (Vácha et al 2010). The As solubility is generally low (Tlustoš et al 2004) and therefore exceeded total content of As in the sediment only slightly increased As mobile fractions. Nevertheless, the risk is regarding total As contents due to human health risk following from inhalation and dermatological As intake from diffuse dust particles (Saha 2003).…”
Section: Resultsmentioning
confidence: 82%
“…Researchers did a great deal of scientific investigation on the harmful effects of As on crops recently, but most of these researches concentrate on one kind of soil or with a certain type of crop [4][5][6][7][8][9][10][11]. Some other works were about phytoremediation of arsenic polluted soils; these researches aim to find a new kind of plant as As-hyperaccumulator [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%